2015
DOI: 10.3390/ijms161226172
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 and Cutaneous Inflammatory Diseases

Abstract: Interleukin (IL)-18, an IL-1 family cytokine, is a pleiotropic immune regulator. IL-18 plays a strong proinflammatory role by inducing interferon (IFN)-γ. Previous studies have implicated IL-18 in the pathogenesis of various diseases. However, it is not well understood biologic activities of IL-18 in the diverse skin diseases. Here, we have reviewed the expression and function of IL-18 in skin diseases including inflammatory diseases. This article provides an evidence-based understanding of the role of IL-18 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 105 publications
1
79
0
1
Order By: Relevance
“…However, improper regulation of IL-18 can potentially lead to inflammation and destruction of self. This cytokine is synthetized as an inactive form that requires to be processed by caspase-1 into its active form [37] .…”
Section: The Il-18 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…However, improper regulation of IL-18 can potentially lead to inflammation and destruction of self. This cytokine is synthetized as an inactive form that requires to be processed by caspase-1 into its active form [37] .…”
Section: The Il-18 Axismentioning
confidence: 99%
“…A growing number of studies support an involvement of the IL-18 axis in the pathogenesis of psoriasis [37] . For reasons not fully understood, patients with an organ-specific autoimmune disease have increased risks of develop-ing autoimmune responses against other organs or tissues.…”
mentioning
confidence: 99%
“…These results suggest that IL-18 is involved in the secretion of TSLP. A previous study reported that secreted IL-18 activated IL-18 receptors to increase the expression of nuclear factor κβ, 47 which induced TSLP production. 48 In addition, skin damage in humans has been reported to induce an increase in TSLP.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose of inflammation is to eliminate the initial causes or damaged cells and begin tissue repair. However, long-term inflammation caused by genetic or environmental factors can lead to chronic cutaneous diseases such as psoriasis, rosacea, atopic dermatitis, and alopecia areata, which are associated with uncontrolled immune activity [19]. A variety of cytokines play an important role in the inflammatory pathogenesis of skin.…”
Section: Roles Of Erythroid Differentiation Regulator 1 (Erdr1) Onmentioning
confidence: 99%
“…In fact, increased expression of IL-18 and its receptor were observed on lesional skin tissues from patients diagnosed with inflammatory cutaneous diseases such as psoriasis, rosacea, atopic dermatitis, or alopecia areata [19]. Moreover, plasma IL-18 concentration has been linked to the severity of these diseases.…”
Section: Roles Of Erythroid Differentiation Regulator 1 (Erdr1) Onmentioning
confidence: 99%